PENGUKURAN KINERJA PERUSAHAAN DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD (Studi Kasus pada CV. Roda Mas Jaya Semarang) - Indra Novanditya; Hari Susanta Nugraha; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2013)
Balanced scorecard has a privilege in terms of coverage measurement is a fairly comprehensive because while taking into consideration the financial performance, balanced scorcard also consider the performance of non-financial performance, namely customer, internal business processes, and learning and growth. Referring to the problems faced by CV. Roda Mas Jaya Semarang, this research examines: "Measurement of Company's Performance by Using the Balanced Scorecard Approach (A Case Study at CV. Roda Mas Jaya Semarang)." Because until now CV. Roda Mas Jaya Semarang has not been using the balanced scorecard to measure performance. Type of research is a case study. The data used inthis study is primary data obtained through focus group discussions and using data collection instruments such as questionnaires. And secondary data from the financial statements for 2009, 2010 and 2011. Data analysis begins with translating the vision and mission into strategic goals, set target and weights through the focus group discussions, performing measurements on each perspective and calculates a score balanced scorecard. Based on the analysis, it could be concluded that the balanced scorecard is a total score 182,73 and in the category of healthy. Perspective of financial, customer perspective and perspective learning and growth in the category of helathy as expected. And perspective of internal business processes in the category not healthy. Advice can be gives to the company is to improve the performance of the nonfinancialaspects, aspecially in the perspective learning and growth.